2018
DOI: 10.1515/intag-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the properties of raw and cooked spaghetti – new indices for pasta quality evaluation

Abstract: The quality of pasta can be evaluated by measuring the characteristics which encompass the most important quality parameters, such as colour, cooking properties and texture. The aim of the study was to suggest new indices which can be used to evaluate the quality of pasta. For the tests, 15 samples of spaghetti (produced from either semolina or common wheat flour) were used. The bending test was performed for the determination of the strength properties of raw pasta, while the pasta colour parameters were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
(9 reference statements)
4
19
0
1
Order By: Relevance
“…It was found that a*, which is associated with redness, diminished with the increasing content of the flaxseed component. An increase in the redness parameter was accompanied by the increase in the ash content [18]. Our results are in agreement with others [18,19]; the redness of the flaxseed-enriched pasta was higher than that of the control sample.…”
Section: Color Parameterssupporting
confidence: 93%
See 4 more Smart Citations
“…It was found that a*, which is associated with redness, diminished with the increasing content of the flaxseed component. An increase in the redness parameter was accompanied by the increase in the ash content [18]. Our results are in agreement with others [18,19]; the redness of the flaxseed-enriched pasta was higher than that of the control sample.…”
Section: Color Parameterssupporting
confidence: 93%
“…An increase in the redness parameter was accompanied by the increase in the ash content [18]. Our results are in agreement with others [18,19]; the redness of the flaxseed-enriched pasta was higher than that of the control sample. The increasing addition of the flaxseed components from 5% to 23% diminished pasta yellowness compared to that of the control sample, i.e., from 20.5 (CON) to 4.1 (FF23) and 3.1 (FC23).…”
Section: Color Parameterssupporting
confidence: 93%
See 3 more Smart Citations